Targeting RNA G-Quadruplexes for potential therapeutic applications - Pandey,Satyaprakash; Agarwala, Prachi; Maiti,Souvik (Topics in Medicinal Chemistry, 2017)
RNA G-quadruplexes are non-canonical structures formed in G-rich regions of transcriptome. Considerable research points towards the potential role for these dynamic structures in various genes involved in multiple pathways. The ability of these structures to influence important biological processes has been demonstrated in few selected important genes and more recently in a global manner across the transcriptome. RNA G-quadruplexes are implicated in fundamental processes such as translational regulation, alternative splicing, mRNA transport and telomere homeostasis to name a few. The involvement of these structures in key biological processes makes them attractive targets for therapeutic interventions. Here we discuss the structural features of RNA G-quadruplex that make it more monomorphic to develop ligands unlike the polymorphic DNA G-quadruplexes. Furthermore, the role of RNA G-quadruplexes in important genes involved in diseases and disorders such as neurodegeneration, cancer and viral infections has been highlighted. A summary of ligands and their established roles in targeting RNA G-quadruplex structures has been discussed in context of important processes. Moreover, we highlight the need to develop ligands that are highly specific in targeting RNA G-quadruplexes, a new target to restore homeostasis in dysregulated conditions.